2018
DOI: 10.1101/393967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novogenesis of retinal ganglion cells by targeted expression of KLF4in vivo

Abstract: Retinal ganglion cell (RGC) degeneration is a hallmark of glaucoma, the most prevalent cause of irreversible blindness. Thus, innovative therapeutic strategies are needed to protect and replace these projection neurons. It has been shown that endogenous glial cells of the retina, Müller cells, can be directly reprogrammed into late-born retinal interneurons. However, since RGCs are the first neurons born during development, the replacement of damaged RGCs requires the reprograming to an early neurogenic state.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Measurements of visual acuity by optomotor response were performed using OptoMotry as previously described ( Cavalheiro et al, 2017 ; Rocha-Martins et al, 2019 ). Experimenters were blind in relation to mice genotypes, and the visual accuracy threshold was determined by systematic increments of the spatial frequency until the animal no longer responded.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of visual acuity by optomotor response were performed using OptoMotry as previously described ( Cavalheiro et al, 2017 ; Rocha-Martins et al, 2019 ). Experimenters were blind in relation to mice genotypes, and the visual accuracy threshold was determined by systematic increments of the spatial frequency until the animal no longer responded.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of visual acuity by optomotor response were performed using OptoMotry as previously described ( Cavalheiro et al, 2017 ; Rocha-Martins et al, 2019 ). Visual accuracy threshold was determined by systematic increments of the spatial frequency until the animal no longer responded.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to redundancy with other Klf family members ( Jiang et al, 2008 ), since many are expressed in the developing retina ( Moore et al, 2009 ; Njaine et al, 2014 ). We recently showed that overexpression of Klf4 in late retinal progenitors generates induced RGCs outside of their developmental window ( Figure 1 ; Rocha-Martins et al, 2019 ). This study showed that Klf4 induced the reactivation of the early neurogenic program in late progenitors, changing their competence to generate RGCs that properly localized to the inner retina and projected axons into the optic nerve head ( Rocha-Martins et al, 2019 ).…”
Section: Molecular Program For Rgc Generationmentioning
confidence: 98%
“…The potential roles of other elements of this network, like fly Krüppel and Pdm , remain unknown. Recently, Klf4 , a member of the family of Krüppel -like factors was studied in the mouse retina, but no critical function in cell fate determination was described ( Moore et al, 2009 ; Fang et al, 2016 ; Rocha-Martins et al, 2019 ). This may be due to redundancy with other Klf family members ( Jiang et al, 2008 ), since many are expressed in the developing retina ( Moore et al, 2009 ; Njaine et al, 2014 ).…”
Section: Molecular Program For Rgc Generationmentioning
confidence: 99%
See 1 more Smart Citation